(untitled) (Международный научный журнал «Инженер», 2026)
This article explores the phase-structural properties and thermal specifications of autoclaved gazobeton samples using industrial waste, including quartz sand and steel smelting slag. The size, shape, and distribution of pores in Gazobeton have been estimated using electron microscopy and radiofascial analysis methods. Based on the results of the experiment conducted, the thermal conductivity coefficient was determined in the range 0.138–0.147 W/(m·°C) in gazobeton samples enriched with industrial waste. The results of the study showed that the optimal size and distribution of pores significantly improves the thermal insulating and mechanical properties of the material. The microstructure and analysis of the mineral phase composition of gazobeton determined its potential to increase energy efficiency and strength indicators.